A long way to go : irregular migration patterns, processes, drivers and decision-making - McAuliffe, Marie; Koser, Khalid (ANU Press, 2017)
A Long Way to Go: Irregular Migration Patterns, Processes, Drivers and Decision-making presents the findings of a unique migration research program harnessing work of some of the leading international and Australian migration researchers on the challenging and complex topic of irregular maritime migration. The book brings together selected findings of the research program, and in doing so it contributes to the ongoing academic and policy discourses by providing findings from rigorous quantitative, qualitative and mixed methods research to support a better understanding of the dynamics of irregular migration and their potential policy implications. Stemming from the 2012 Expert Panel on Asylum Seekers report, the Irregular Migration Research Program commissioned 26 international research projects involving 17 academic principal researchers, along with private sector specialist researchers, international organisations and policy think tanks. The centrepiece of the research program was a multi-year collaborative partnership between the Department of Immigration and Border Protection and The Australian National University's Crawford School of Public Policy. Under this partnership, empirical research on international irregular migration was commissioned from migration researchers in Australia, Indonesia, Iran, the Netherlands, Sri Lanka and Switzerland.